Survival by histologic subtype in stage IV nonsmall cell lung cancer based on data from the Surveillance, Epidemiology and End Results Program - Hei Y; Ettinger DS; Cetin K; O'Malley CD (Clinical Epidemiology, 2011)
Karynsa Cetin1, David S Ettinger2, Yong-jiang Hei3, Cynthia D O'Malley11Center for Observational Research, Amgen Inc., Thousand Oaks, CA, USA; 2Sidney Kimmel Comprehensive Cancer Center, Johns Hopkins University, Baltimore, MD, USA; 3Global Development, Amgen Inc., Thousand Oaks, CA, USABackground: The role of histology in the targeted management of nonsmall cell lung cancer (NSCLC) has garnered renewed attention in recent years. We provide contemporary population-based estimates of survival and an assessment of important prognostic factors in stage IV NSCLC by major histologic subtype.Methods: Using data from the Surveillance, Epidemiology and End Results (SEER) Program, we stratified 51,749 incident stage IV NSCLC patients (1988–2003 with follow-up through 2006) by major histologic subtype. We used Kaplan–Meier and Cox proportional hazards methods to describe overall survival and the prognostic influence of select patient, tumor, and treatment characteristics for each histologic subgroup.Results: Survival was highest in patients with bronchioloalveolar adenocarcinoma (1-year survival: 29.1%) and lowest in those with large cell tumors (1-year survival: 12.8%). Diagnosis in later years, female gender, younger age, either Asian/Pacific Islander or Hispanic race/ethnicity, lower tumor grade, and surgery or beam radiation as part of first-line treatment were generally independently associated with a decreased risk of death, but the prognostic significance of some of these factors (age, ethnicity, tumor grade) varied according to histologic subtype.Conclusion: Findings demonstrate a poor prognosis across histologic subtypes in stage IV NSCLC patients but highlight differences in both absolute survival and the relative importance of select prognostic factors by histologic subclassification. More research using other sources of population-based data could help clarify the role of histology in the presentation, management, and prognosis of late-stage NSCLC.Keywords: epidemiology, nonsmall cell lung cancer, histology, survival